2019
DOI: 10.1029/2018ja025684
|View full text |Cite
|
Sign up to set email alerts
|

Transient Oscillations Near the Dayside Open‐Closed Boundary: Evidence of Magnetopause Surface Mode?

Abstract: Geomagnetic pulsations in Pc5-6 band (~3-20 min) are persistent feature of ULF activity at dayside high latitudes. Magnetopause surface eigenmodes may be suggested as potential mechanism of these pulsations. One might expect the ground response of these modes to be near ionospheric projection of the open-closed field line boundary (OCB). Using data from instruments located at Svalbard we study transient geomagnetic response to impulsive "intrusion" of magnetosheath plasma into the dayside magnetosphere. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(53 citation statements)
references
References 62 publications
6
46
0
Order By: Relevance
“…Throat aurora has been suggested to correspond to a magnetopause indentation that is caused by magnetopause reconnection (Han et al, 2019). We found that all the auroras shown in Kim et al (2017), Kozyreva et al (2019), and Mende et al (2001) have clear throat aurora features. We argue that the geomagnetic responses discussed in these studies should correspond to localized magnetopause indentations that are caused by magnetopause reconnection.…”
Section: Summary and Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Throat aurora has been suggested to correspond to a magnetopause indentation that is caused by magnetopause reconnection (Han et al, 2019). We found that all the auroras shown in Kim et al (2017), Kozyreva et al (2019), and Mende et al (2001) have clear throat aurora features. We argue that the geomagnetic responses discussed in these studies should correspond to localized magnetopause indentations that are caused by magnetopause reconnection.…”
Section: Summary and Discussionsupporting
confidence: 56%
“… d. Compare with previous studies on geomagnetic transients near local noon . Geomagnetic transients observed at high latitudes on the dayside have been extensively studied, including, MIE (Lanzerotti et al, 1990), TCV (Chaston et al, 1993; Friis‐Christensen et al, 1988; Glassmeier et al, 1989; Shi et al, 2014; Zesta, 2002), and impulsive ULF waves (Kozyreva et al, 2019; Lyatsky & Sibeck, 1997; Olson, 1986; Shen et al, 2018). MIEs have been generally accounted for geomagnetic responses to the transient variations in the IMF or solar wind pressure (Kataoka, 2003; Kawano et al, 1992; Lanzerotti et al, 1990; Lin et al, 1995; Mende et al, 1990; Sibeck & Croley, 1991).…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Observations in both the topside ionosphere and the plasmasphere showed that the radial width of the plasmapause was 0.1-0.2 R E (see Supplementary Figs. 6, 7), which was much smaller than the transverse wave scale of~0.8 R E for the PSW with m-value at a geocentric distance of 4.5 R E , satisfying the requirement of the interface width in exciting surface waves 47 . The sharp discontinuity in the density led the magnetosonic wave to be undamped 24,46,48 , allowing excitation of a standing surface eigenmode, i.e., the PSW propagating sunward/westward at the plasmapause boundary and along the field lines to both the northern and southern polar ionosphere.…”
Section: Discussionmentioning
confidence: 73%